SPATIAL DISTRIBUTION OF PHYTOPLANKTON AT THE HURUN BAY, LAMPUNG - Darmawan, Rahmania A (Jurnal Hidrosfir Indonesia, 2008)
It is already known that several ecological factors affected phytoplankton distribution in coastal waters, but since the global increase of Harmful Algal Blooms (HABs) phenomenon, people pay more attention on nutrient enrichment. Previous researches showed that HABs phenomenon was happened at the Lampung Bay, especially Trichodesmium erythraeum and Pyrodinium bahamense (Widiarti, 2000). This study was focus on spatial distribution of phytoplankton around the Hurun Bay. Seventeen sampling sites were investigated for phytoplankton assessment and the result showed that a high phytoplankton distribution was found close to coastal area andgetting decreased toward offshore. This phenomena was support by total phosphate concentration where their high concentration was found close to coastal area. During the observation, it was found that Leptocyindricus dominate the area beside Chaetoceros, which was also dominance at the station 8. Total nitrogen and dissolved oxygen distribution were almost the same among those stations. Furthermore, it could be concluded as well that Hurun Bay was tend to phosphate limited area.